Highway engineering - Wright, Paul H. (New York : John Wiley and Sons, 1996)
This book presents to readers about planning, design, construction, operation, and maintenance of highways which depend largely on the efforts of the highway engineer, who must translate the desires of the people for better highway transportation into physical being.
Keywords: Highway engineering; Highway engineering